PENGARUH METODE SURVEY, QUESTION, READ, RECITE, REVIEW TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN - Vivin Rosadi; Syambasril Syambasril; Siti Halidjah (Universitas Tanjungpura, 2020)
Abstract The main issue on this article discusses how the influence of the use of survey, questions, read, recite, review (SQ3R) method on students' reading comprehension skills. The research method is used quasi-experimental method with a nonequivalent control group design. The population in this study was all fifth grade students of Sadayan 07 Public Elementary School, totaling 41 students. Based on the results of research analysis, the average post-test score of the experimental class was 62.36 while the average post-test score of the control class was 53.93. Based on the results of the t-test calculation, the tcount was 2,351 and the t-table was 2,027. Because tcount (2,351) > ttable (2,027), Ha is accepted. Based on the Effect Size calculation, the result is as high as 0.66 in the medium criteria. So it can be concluded that the application of survey, question, read, recite, and review methods have a positive influence on the reading skills of students in grade V at Sadayan 07 Public Elementary School. Keywords: Influence, Reading Comprehension, SQ3R Method